A new species of Bursera (Burseraceae) from the East Cape Region in Baja California Sur, Mexico - León de la Luz, José Luis; Medel Narváez, Alfonso; Domínguez Cadena, Reymundo (Instituto de Ecología, A.C., 2017)
Background and Aims: Intensive fieldwork along the shore of the East Cape Region in the Baja California Peninsula by the authors has resulted in the discovery and publication of some new species for the Mexican flora in recent years.Methods: An additional novelty found was a tree considered at first to be Bursera microphylla, but a more detailed inspection showed the leaflets to be few in number and broadly obovate-elliptic. These and additional differences of the leaves and flowers warrant recognition of this plant as a new species.Key results: We here describe and illustrate Bursera exequielii (Burseraceae), which belongs to section Bursera and we discuss its morphological relationship with B. microphylla, from which it differs mainly by the number, form and size of the leaflets.Conclusions: The only known population is threatened due to the mega-touristic developments in the zone.